A review of research on student self-assessment in second / foreign language writing - Bhatti, Nasreen; Nimehchisalem, Vahid (State Islamic Institute of Samarinda, 2020)
The present article reviews the research on writing Self-Assessment (SA) conducted in the period of 2000 - 2020. The article discusses the theoretical foundation for SA following the review of conceptualization of SA by various researchers. We were particularly interested in (i) examining whether the concept of SA has witnessed an expansion during the two decades in English as a foreign/second language (EFL/ESL) writing and (ii) determining the components that were found interconnected to the concept of SA in the writing context. The findings related to the first objective indicate that the SA has expanded in its conceptualization; however, its definition and application are expected to broaden. As a result of analyzing the studies, based on the second objective, the following themes emerged: SA and training students, SA and the dialogue between students and teachers, SA and teacher training, SA and affective variables, SA and cultural components, SA and age, SA and instrumentation, SA and exemplars, SA and teacher feedback, SA and prior experience, SA and conducive environments, SA and contextualizing SA items. The review shows an important role of the components in the concept of SA in the EFL/ESL writing context; however, studies in this regard are scarce. Another group of studies that emerged was those that examined perceptions towards SA. We conclude with a critical reflection on the reviewed literature and recommend new directions for further studies.